Geopolitics of Energy in the Caspian Sea Region: Azerbaijan's Challenges - Ilgar, Mammadov (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: In the age of rapid economic development and uneven allocation of hydrocarbon resources around the world, acute need for their transportation and amplified energy dependency world politics is and will in the coming years be increasingly dominated if not determined by the energy. Contest to gain access to the Caspian energy and rivalry about transportation routes should be viewed within this context. In addition to their own merit the hydrocarbon resources of the Caspian Sea are used by external players for broader objectives of dominance and influence, while the local actors brought them into play for economic development, social welfare, political consolidation, creation of forthcoming and stable regional environment and integrating into world economy. International players making use of their financial potential and political influence, sometimes even military strength, and the Caspian countries proceeding from their complex political surrounding and taking advantage of their resources and favorable geographic location resorted to geopolitics in pursuit of their ends. Turkic-Mongol empires dominated Eurasia during the centuries promoted and facilitated extensive trade, economic, cultural, religious, scientific exchanges across continent along the trade routes known as Great Silk Road. These connections in huge landmasses of Eurasia were possible in addition to such values as tolerance and mutual respect due to perfect communications means. 21st century presents another opportunity for such exchanges, this time through energy links. The Caspian Sea should be region uniting, not dividing Eurasia through co-operation and partnership, not rivalry and opposition. The Caspian is pivot of Heartland. Who co-operates in the Caspian commands Eurasia.